PENGARUH PARTISIPASI PENGANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN BUDAYA ORGANISASI DAN JOB RELEVANT INFORMATION SEBAGAI PEMODERASI - Sucitrawati, I Gusti Ayu; Ratna Sari, Maria M. (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
This study aims to determine the effect on performance budgeting partisipai manajerialdan variables influence organizational culture and job relevant information in relation moderate budgetary participation on managerial performance. Research conducted at the regional work units Badung and population used in this study is the official head of the structural level / field in Badung regency SKPD. The sample was 86 people determined using purposive sampling method. Data research data sourced from questionnaires distributed to respondents and data analysis techniques used are moderate regression analysis. The results of their research analysis found a positive effect of participation budgeting on managerial performance, organizational culture capable of moderating and strengthen the relationship between budgetary participation on managerial performance and job relevant information was not able to moderate and weaken the relationship between budgetary participation on managerial performance.
Keywords: Budgeting Participation, Managerial Performance, Organizational Culture, Job Relevant Information